Factors affecting exposure level for medical staff during orthopedic procedures under fluoroscopic control - Maria A. Staniszewska; Renata Kopeć; Maciej Budzanowski; Edyta Owsiak (Nofer Institute of Occupational Medicine, 2017)
Background: Extended control of staff exposure in interventional radiology has been legally required over the last few years. This is determined by a number of factors, including the type of procedure, technical conditions and methodology. In orthopedic procedures fluoroscopy is used to control surgical reconstructions. An influence of particular factors on the registered values of doses received by the members of medical team performing osteosynthesis for limb fractures is presented in this paper. Material and Methods: Doses received by individual interventional team members performing specific functions, operator, assisting physicians and scrub nurse, during a series of the procedures were measured. Each person was equipped with 4 dosimetric tools, containing thermoluminescent dosimeters, to measure the equivalent doses for the eyes, hand skin and the neck (outside the shield) and to evaluate effective doses. The investigations were performed in operational theatres of 3 hospitals in Łódź. Results: The equivalent doses per one procedure for the eyes and hand skin of the operator were 0.029-0.073 mSv and 0.366-1.604 mSv, respectively. Significantly higher doses were noted during the procedures of intramedullary osteosynthesis, especially for the operator. An average age and body mass index (BMI) of patients treated in the monitored hospitals did not differ statistically. Conclusions: Based on the dosimetric measurements the following conclusions can be drawn: in orthopedic procedures of interventional radiology (IR) the exposure of the staff is mostly determined by the type of procedure and more precisely by its complexity and by the optimized use of X-ray unit, including pulsed fluoroscopy. It is also revealed that the operator is the most exposed person in the interventional team. Med Pr 2017;68(1):75-83